2012
DOI: 10.1111/1365-2656.12012
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on light: benefits of anthropogenic illumination to a nocturnally foraging shorebird

Abstract: Summary1. Intertidal habitats provide important feeding areas for migratory shorebirds. Anthropogenic developments along coasts can increase ambient light levels at night across adjacent inter-tidal zones. Here, we report the effects of elevated nocturnal light levels upon the foraging strategy of a migratory shorebird (common redshank Tringa totanus) overwintering on an industrialised estuary in Northern Europe. 2. To monitor behaviour across the full intertidal area, individuals were located by day and night… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 40 publications
0
84
0
1
Order By: Relevance
“…[41,42]), physiology (e.g. [43][44][45][46]), foraging [24,[47][48][49][50], daily movements [51][52][53][54][55], migratory behaviour (e.g. [56,57]), reproductive behaviour (e.g.…”
Section: Individual Organismsmentioning
confidence: 99%
“…[41,42]), physiology (e.g. [43][44][45][46]), foraging [24,[47][48][49][50], daily movements [51][52][53][54][55], migratory behaviour (e.g. [56,57]), reproductive behaviour (e.g.…”
Section: Individual Organismsmentioning
confidence: 99%
“…Such physiological responses to ALAN might differ between urban and rural animals, and suggest the possibility that at least some species might adapt to and thus tolerate the presence of artificial lights. Indeed, bright nights can also offer opportunities, for example extending foraging time found for a number of diurnal species (Santos et al, 2010;Dwyer et al, 2013;Russ et al, 2015;Dominoni et al, 2016), thereby likely providing fitness benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Although the behavioural data previously collected on several avian species had already suggested that light pollution might affect the detection of daylength [15,27,28,41,42], here we used advances in radio-telemetry and bio-logging technology to test this hypothesis directly. Altogether, our results suggest that birds thriving in highly light-polluted areas are exposed to a light environment that could be perceived as a longer photoperiod than in other nearby, but darker, regions.…”
mentioning
confidence: 99%